Colloidchemical properties of polimer-monomer particles on boundary of monomer/water - I. A. Gritskova; G. A. Simakova; N. I. Prokopov; T. S. Solovyeva; E. V. Matveev; A. S. Birlov (Тонкие химические технологии, 2009)
Colloid-chemical properties of surface active substances of different nature on the boundary of styrene/water, isoprene/water, mixture of styrene and isoprene/water are discussed. It was shown that the mechanism of creation polymer-monomer particles are depending from composition of emulsion